The Tractatus Logico Philosophicus: a wild paradox - Garmendia, Santiago (Analysis. Journal of Philosophical Research, 2021)
The Tractatus, one hundred years after its publication, is probably the most commented and discussed book of the 20th century. Our idea is that the architectural base of the text is something that we call Language-Subject-World inseparability. It is not an original idea, but the contribution lies in the fact that we maintain that it is a thesis that unfolds in a curious way. We will be emphatic regarding the form of presentation, because we want to emphasize that the Tractatus is not static, but dynamic. I would ponder a moment in exegetical history in the nineties, where such enormously divergent paths open up. The New American Reading and the Essentialism of R. Bradley. Exegetical history has many literal readings, perhaps Bradley´´ s is the most metaphysical of all, while what we can call a "dynamic" interpretation, that of Diamond-Conant, has turned it into a rhetorical experiment. We hope to be neither literal static nor ironic dynamics, but dialectical insofar as that the Tractatus can be read as a series of movements, affirmations and denials that seek to establish the thesis of inseparability.